2014
DOI: 10.4103/0976-237x.128675
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of microleakage in conventional glass ionomer cements and triclosan incorporated glass ionomer cements

Abstract: Aim and Objective:The aim of the following study is to comparatively evaluate the microleakage of triclosan incorporated GIC with conventional restorative GIC.Materials and Methods:Triclosan in powder form was added to conventional GIC to formulate a concentration of 2.5%. Class five cavities were prepared in non-carious extracted molars and were respectively restored with conventional restorative GIC and triclosan incorporated GIC. Samples were kept in 10% methylene blue dye. Ground sections were obtained and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Incorporation of EGCG to dental adhesives it did not affect the durability of the bond [168]. Addition of triclosan also had positive results, when added to GIC did not increase microleakage of the material [163] and its addition to adhesives did not affect adhesion [162].…”
Section: Other Additivesmentioning
confidence: 73%
See 1 more Smart Citation
“…Incorporation of EGCG to dental adhesives it did not affect the durability of the bond [168]. Addition of triclosan also had positive results, when added to GIC did not increase microleakage of the material [163] and its addition to adhesives did not affect adhesion [162].…”
Section: Other Additivesmentioning
confidence: 73%
“…Other additives to composites and GICs found to be effective against cariogenic bacteria include cetylpyridium chloride, cetrimide [148,150,155,156], benzalkonium chloride [95,146], sodium fusidate [157], 2,2 -bipyridine [158], chitosan [159,160], triclosan [66,149,[161][162][163], propolis [164,165], anthocyanin [166], tetrapod-like zinc oxide whisker (T-ZnOw) [167] and epigallocatechin-2-gallate (EGCG) [11,168,169]. In contrast to most of the other additives, addition of T-ZnOw epigallocatechin-2-gallate resulted in improved mechanical properties [11,167].…”
Section: Other Additivesmentioning
confidence: 99%
“…Yet, the effect of adding the triclosan into GICs on the physical and mechanical properties of GICs has not been investigated in this study. In the following years, Somani et al 159 reported that microleakage of 2.5% triclosan incorporated GICs were similar to the conventional GICs. Shear bond strength of 2.5% triclosan incorporated GICs was also higher than conventional GICs.…”
Section: Triclosanmentioning
confidence: 95%
“…Sainulabdeen et al 153 In vitro Modified GIC was more effective against L. acidophilus and S. mutans than chlorhexidine incorporated GIC Physical and mechanical properties of modified GIC have not been investigated Somani et al 159,160 In vitro The antibacterial properties of triclosan incorporated GIC of has not been evaluated…”
Section: ) Triclosanmentioning
confidence: 99%
“…Microleakage of 2.5% triclosan-incorporated GIC was compared with conventional type II GIC and the results revealed that microleakage was similar to that of conventional GIC. 44,45 The idea is to enhance the antimicrobial properties of GICs with a balanced dose of additives incorporated into the compound, without causing biological, physical and chemical changes of a biomaterial. It is suggested that these restorative materials can be used as controlledrelease devices, a topic of great interest in modern day pharmacy.…”
Section: Introductionmentioning
confidence: 99%